BIPOLAR ANALYSIS IN THE CHARACTER OF ATHUR FROM THE NOVEL FANGIRL BY RAINBOW ROWELL: Bipolar Disorder, Conflict, Character - Danu Wahyono (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2022)
This research tells about a character named Arthur where he suffers from bipolar episodes which require him to commit to the hospital and take medication, and also makes him tell his daughters to live their own lives, but there is anxiety experienced by him. Arthur told his daughter because there were some problems that happened at her daughter's school, and there were some problems that made her depressed, namely when he had a fight with his wife in the past and caused their family to fall apart due to divorce. and in this analysis it is also explained that the cause and effect of a bipolar episode where Arthur suffers from severe depression due to the problems he suffers that comes from his daughter.